The Mechanism of APOBEC3B in Hepatitis B Virus Infection and HBV Related Hepatocellular Carcinoma Progression, Therapeutic and Prognostic Potential - Yang X; Wang H; Yu C (Infection and Drug Resistance, 2024)
Xiaochen Yang,* Huanqiu Wang,* Chengbo Yu State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, Hangzhou, Zhejiang, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chengbo Yu, State Key Laboratory for Diagnosis and Treatment of Infectious Diseases, National Clinical Research Center for Infectious Diseases, Collaborative Innovation Center for Diagnosis and Treatment of Infectious Diseases, The First Affiliated Hospital, School of Medicine, Zhejiang University, 79 Qingchun Road, Hangzhou, Zhejiang, 310003, People’s Republic of China, Tel +86-571-87236458, Email yuchengbo1974@zju.edu.cnAbstract: Hepatocellular carcinoma (HCC) is one of the most prevalent malignant tumors globally. Prominent factors include chronic hepatitis B (CHB) and chronic hepatitis C (CHC) virus infections, exposure to aflatoxin, alcohol abuse, diabetes, and obesity. The prevalence of hepatitis B (HBV) is substantial, and the significant proportion of asymptomatic carriers heightens the challenge in diagnosing and treating hepatocellular carcinoma (HCC), necessitating further and more comprehensive research. Apolipoprotein B mRNA editing catalytic polypeptide (APOBEC) family members are single-stranded DNA cytidine deaminases that can restrict viral replication. The APOBEC-related mutation pattern constitutes a primary characteristic of somatic mutations in various cancer types such as lung, breast, bladder, head and neck, cervix, and ovary. Symptoms in the early stages of HCC are often subtle and nonspecific, posing challenges in treatment and monitoring. Furthermore, this article primarily focuses on the established specific mechanism of action of the APOBEC3B (A3B) gene in the onset and progression of HBV-related HCC (HBV-HCC) through stimulating mutations in HBV, activating Interleukin-6 (IL-6) and promoting reactive oxygen species(ROS) production, while also exploring the potential for A3B to serve as a therapeutic target and prognostic indicator in HBV-HCC.Keywords: hepatocellular carcinoma, hepatitis B virus, APOBEC3B, chronic hepatitis B